Lingkungan Pendidikan Islam Berbasis Hadis Tarbawi dalam Perspektif Pendidikan Kontemporer - Dini Widiyastutik; Alif Nur Hanifah; Ahmad Yusam Thobroni; M Baihaqi (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2025)
Abstract: Contemporary education faces serious challenges, including value fragmentation, moral decline, the reduction of educational environments to merely physical spaces, and the dominance of pragmatic–instrumental approaches in learning practices. At the same time, studies on educational environments from an Islamic perspective—particularly those based on hadith tarbawi—remain largely normative and have yet to be developed into frameworks that address modern educational issues. This study aims to analyze and reconstruct the concept of educational environments derived from hadith tarbawi in a manner aligned with contemporary educational needs. The research employs library research using thematic hadith analysis (maudhu‘i) combined with critical examination of contemporary educational literature. The findings indicate that hadith tarbawi contains a holistic conception of educational environments encompassing spiritual, social, moral, and educative dimensions. This conception positions educators as moral exemplars, learners as subjects of continuous cultivation, and the environment as a space for value internalization and character formation. The novelty of this study lies in offering a conceptual framework that bridges prophetic values with modern educational challenges. It contributes theoretically to the development of Islamic education that is more integrative, contextual, and character-oriented.